Layer-by-layer gelatin/chitosan polyelectrolyte coated nanoparticles on Ti implants for prevention of implant-associated infections - T. Sangfai; F. Dong; V. Tantishaiyakul; K. D. Jandt; C. Ludecke; O. Boonrat; N. Hirun (eXPRESS Polymer Letters)
Gelatin nanoparticles (Gb-NP) and layer-by-layer (LBL) coated NPs were developed to modify a Ti substrate surface to prevent implant-associated infections. Vancomycin (Van) was loaded into these materials to obtain GbV-NP and LBL-GbV-NP. The size of the GbV-NP (277.4±1.4 nm) was smaller than that of LBL-GbV-NP (710.2±4.6 nm) but both had a spherical shape. These coated materials showed no cytotoxicity and facilitated better cell proliferation by osteoblast-like cells compared to the bare Ti. This was probably due to the roughness of the coated NP that enhanced cell attachement to the surface. Both coated materials showed antibacterial activity against S. aureus. The release of Van from GbV-NP was higher from LBL-GbV-NP and this corresponded to their antibacterial activity. Furthermore the release profile of Van showed a sustained release. Thus both materials should be able to prolong the protection of implant-associated infections to the bone.